Progress in the pathogenic mechanism, histological characteristics of hereditary dentine disorders and clinical management strategies - Xue, Qing; Wu, Zhina; Zhao, Yinuo; Wei, Xiaoxi; Hu, Min (Frontiers in Cell and Developmental Biology, 2024)
Hereditary dentine disorders are autosomal dominant diseases that affect the development and structure of dentine, leading to various dental abnormalities and influencing the individual’s oral health. It is generally classified as dentinogenesis imperfecta (DGI) and dentine dysplasia (DD). Specifically, DGI is characterized by the abnormal formation of dentine, resulting in teeth that are discolored, translucent, and prone to fracture or wear down easily. DD is characterized by abnormal dentine development, manifested as teeth with short roots and abnormal pulp chambers, leading to frequent tooth loss. Up to now, the pathogenesis of hereditary dentine disorders has been poorly clarified and the clinical intervention is limited. Treatment for hereditary dentine disorders focuses on managing the symptoms and preventing further dental problems. Genetic counseling and testing may also be recommended as these conditions can be passed on to future generations. In this review, we summarize the clinical features, pathogenic genes, histomorphological characteristics and therapy of hereditary dentine disorders. Due to the limited understanding of the disease at present, we hope this review could improve the recognition of the disease by clinicians, stimulate more scholars to further study the deeply detailed mechanisms of the disease and explore potential therapeutic strategies, thus achieving effective, systematic management of the disease and improving the life quality of patients.